Pengembangan Modul Pembelajaran IPA Berbasis Etnosains Materi Pencemaran Lingkungan Untuk Melatih Literasi Sains Siswa Kelas VII di SMP - Mardianti, Iis; Kasmantoni, Kasmantoni; Walid, Ahmad (BIO-EDU: Jurnal Pendidikan Biologi, 2020)
Abstract: The purpose of this research is to develop ethnics-based science learning modules that have the feasibility to be used after validation. The research method uses the Borg & Gall development model which consists of 8 stages, namely a preliminary study stage, a research planning stage, a design development stage, a limited field test stage, a revised stage of the results of a limited field test stage, a broad trial phase, a revision stage of the trial results from wider field and the final product stage. This research is limited to the develop stage, namely the feasibility of the module. The instrument used was a questionnaire for module eligibility. The research subjects were 3 lecturers of Islamic religious institutes consisting of 1 language expert lecturer, 1 material expert lecturer, and 1 media expert lecturer. The data from the questionnaire analysis by calculating the percentage of achievement in each component of the percentage of achievement criteria for the feasibility of learning modules based on ethnics-based science developed is suitable for use with a percentage of 88%, 77.5%, 87.5% (very feasible, feasible, and very feasible categories). From the results of these data, it can be concluded that the module is feasible to be used as teaching material in supporting the teaching and learning process on environmental pollution material.